2015
DOI: 10.1186/s13031-015-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Katana referral hospital as a complex adaptive system: agents, interactions and adaptation to a changing environment

Abstract: This study deals with the adaptation of Katana referral hospital in Eastern Democratic Republic of Congo in a changing environment that is affected for more than a decade by intermittent armed conflicts. His objective is to generate theoretical proposals for addressing differently the analysis of hospitals governance in the aims to assess their performance and how to improve that performance. The methodology applied approach uses a case study using mixed methods ( qualitative and quantitative) for data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In the DR Congo, the health zone is a set of health centers linked to a hospital. 28 In each of the selected health zones, the samples were collected first from the main hospital of that zone. When this was a government-operated general referral hospital, medicines were sampled also from the nearest church health center, private pharmacy, and informal vendor of medicines.…”
Section: Methodsmentioning
confidence: 99%
“…In the DR Congo, the health zone is a set of health centers linked to a hospital. 28 In each of the selected health zones, the samples were collected first from the main hospital of that zone. When this was a government-operated general referral hospital, medicines were sampled also from the nearest church health center, private pharmacy, and informal vendor of medicines.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, medical service organizations of different levels should establish collaborative standards in terms of system, environment and service so as to enhance the experience of patients. Similarly, research by Karemere H [ 18 ] also demonstrated that referral performance depends on the institutional arrangements of the intermediary agency and their ability to adapt to demands. Additionally, Kurtzman [ 19 ] focused on the impact of the regional environment on the practice of healthcare practitioners and found that the referral environment is a factor influencing the service provided by nurses; therefore, local referral services should be conducted in an organized manner.…”
Section: Discussionmentioning
confidence: 98%
“…Although health care systems have been acknowledged as CAS by many scientists [23,26,27,29,36,39,41], it seems that it has rarely been translated into practice. Considering a paradigm shift toward description of health care systems as complex systems in recent years and insu ciency of the traditional approaches, it is therefore worthwhile to explore the premises of complexity science to approach health care problems.…”
Section: De-central Control Of the Agentsmentioning
confidence: 99%
“…Recently complexity science approach to health, settings and organizations has emerged as a promising approach which can provide a more thorough understanding of complex health issues [24][25][26][27][28][29]. Similarly, applying the Complex Adaptive Systems (CAS) theory, a derivative of complexity science to understand, explore, scale up, evaluate and research in health systems has become popular with researchers in recent years [22,[30][31][32][33].…”
mentioning
confidence: 99%